Computing Waste Management Using Cloud Platform and Sensors - M. , Govindaraj; Ramachandran, Vedanth (International Journal of Psychosocial Rehabilitation, 2020)
A happy and hazard-free development of our city promotes growth in the field of information and communication technology. The issue of waste and hazardous garbage in our city has caused an acute problem of managing it. We see that we have a number of garbage trucks roaming around in our city, collecting waste, which has turned out to be inefficient, as we see that some of them may have turned away from their given responsibilities and tasks, due to which we face difficulty in the procedure of the conventional waste collection approach. The purpose of this paper is to introduce an efficient and technological waste management system that will enable us to handle the process dynamically and provide the best way to utilize manpower efficiently. In our model approach, the weighted and volume waste that are thrown in the waste bins are collected by economical sensors and then sent to a cloud server using a micro-controller and GPRS. This data is used to find the waste collected and report to the system about the area and location. This phenomenon could help the team to collect the lump sum waste by locating the nearest vehicles and scheduling a task to clear up the waste bins and by sharing with the driver the shortest route possible . This paper proposes a model to keep our city free from garbage, therefore ensuring good health for all.